2010
DOI: 10.1103/physrevb.81.024102
|View full text |Cite
|
Sign up to set email alerts
|

Theory of quantum paraelectrics and the metaelectric transition

Abstract: We present a microscopic model of the quantum paraelectric-ferroelectric phase transition with a focus on the influence of coupled fluctuating phonon modes. These may drive the continuous phase transition first order through a metaelectric transition and furthermore stimulate the emergence of a textured phase that preempts the transition. We discuss two further consequences of fluctuations, firstly for the heat capacity, and secondly we show that the inverse paraelectric susceptibility displays T^2 quantum cri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…x O 1−x ) 3 has been studied for varying x at very low temperatures at ambient pressure; because it does not depend strongly on sample growth conditions or purity, it has been suggested that disorder is not a key feature [22]. The detailed behavior of the dielectric response is in excellent agreement with theoretical predictions [9,17,18,19,20,22,59,60,77,82], suggesting that this is a system where detailed interaction between theory and experiment are possible. Work is currently in progress on the Grüneisen ratio [66] in this same set of materials to explore its behavior at and in proximity to the DFE-QCP (displacive ferroelectric quantum critical point) [67].…”
Section: The Case Of Srt Io 3 To Datementioning
confidence: 77%
See 1 more Smart Citation
“…x O 1−x ) 3 has been studied for varying x at very low temperatures at ambient pressure; because it does not depend strongly on sample growth conditions or purity, it has been suggested that disorder is not a key feature [22]. The detailed behavior of the dielectric response is in excellent agreement with theoretical predictions [9,17,18,19,20,22,59,60,77,82], suggesting that this is a system where detailed interaction between theory and experiment are possible. Work is currently in progress on the Grüneisen ratio [66] in this same set of materials to explore its behavior at and in proximity to the DFE-QCP (displacive ferroelectric quantum critical point) [67].…”
Section: The Case Of Srt Io 3 To Datementioning
confidence: 77%
“…It was assumed that the stability of the paraelectric state in low temperature STO is due to effects of zero-point fluctuations analogous to the situation in liquid helium where crystallization is never achieved at ambient pressure. There was already prior theoretical literature on the effects of quantum fluctuations on low temperature displacive transitions [16,17,59,60,62], and experiments on STO stimulated more theoretical research in this direction [9,18,19,20,22,80,81,82]. Usually one associates zero-point fluctuations with light atoms like hydrogen or helium so their significance for STO may seem surprising.…”
Section: The Case Of Srt Io 3 To Datementioning
confidence: 99%
“…10 It has been suggested that EuTiO 3 is the prototype for studying quantum paraelectric behavior in magnetic systems. 11 In addition to these experiments on bulk EuTiO 3 , there has been a series of recent studies on EuTiO 3 thin films [12][13][14][15] motivated in part by the subsequently verified prediction that epitaxial strain should induce ferroelectricity and multiferroicity. 16,17 Likewise "chemical strain," i.e., doping at the A site with larger divalent ions, has been shown to induce ferroelectricity, e.g., in alloys with BaTiO 3 .…”
Section: Introductionmentioning
confidence: 99%
“…The bosonic propagator describing the FE fluctuations in the disordered state is given by [12,30,31,37,38]…”
Section: A Bosonic Propagator: Optical Phononsmentioning
confidence: 99%